2017
DOI: 10.1159/000475535
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mechanical Thrombectomy in the M1 and M2 Segments of the Middle Cerebral Artery: A Review of 585 Consecutive Patients

Abstract: Background: Mechanical thrombectomy for anterior-circulation large-vessel occlusion has shown benefit; however, the question of whether this technique is safe and effective in the distal vasculature remains unanswered. We sought to compare the outcome data from mechanical thrombectomy of the M2 branches of the middle cerebral artery (MCA) with those of the M1 segment. Methods: We performed a retrospective analysis of prospectively collected data of patients with acute ischaemic stroke undergoing mechanical thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
6
31
1
1
Order By: Relevance
“…10 Several retrospective studies examining EVT for M2 occlusions found similar or greater rates of successful revascularization (mTICI 2b/3) and good functional outcome (mRS 0-2) at follow-up as compared to M1 occlusions. [11][12][13][14] In a retrospective study of patients with M2 occlusions, Sarraj et al 15 found that EVT resulted in significantly greater odds of functional improvement compared to medical management. Additionally, a meta-analysis of data from the HERMES collaboration examining outcomes of EVT in M2 MCA occlusions compared to medical management found a treatment effect in favor of EVT regarding good functional outcome (mRS 0-2 at 90 days).…”
Section: Introductionmentioning
confidence: 99%
“…10 Several retrospective studies examining EVT for M2 occlusions found similar or greater rates of successful revascularization (mTICI 2b/3) and good functional outcome (mRS 0-2) at follow-up as compared to M1 occlusions. [11][12][13][14] In a retrospective study of patients with M2 occlusions, Sarraj et al 15 found that EVT resulted in significantly greater odds of functional improvement compared to medical management. Additionally, a meta-analysis of data from the HERMES collaboration examining outcomes of EVT in M2 MCA occlusions compared to medical management found a treatment effect in favor of EVT regarding good functional outcome (mRS 0-2 at 90 days).…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 , 10 ] However, because of the circuit in which the distal artery is included and the small vascular diameter, it is difficult for existing techniques, including aspiration (even via aspiration catheter), to reach the desired location and provide effective therapy. [ 6 ] Recently, micro-ADAPT technology was developed. [ 15 ] Although this technology provides a rapid and effective technique for thrombus extraction from the A3, M3, and P3 segments, it is difficult for finer vascular aspiration catheters to be positioned in contact with the thrombus for suction.…”
Section: Discussionmentioning
confidence: 99%
“…These reports provide evidence suggesting that this therapy is insufficient is some cases and is associated with a considerable risk of operation-related complications such as vasospasm, dissection, and perioperative bleeding. [ 5 , 6 , 8 12 ] Tirofiban is a reversible, nonpeptide platelet glycoprotein IIb/IIIa receptor antagonist. While it is mainly used to treat unstable angina and in coronary angioplasty, its potential use for acute thrombosis and stent implantation during neuro-interventional surgery has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…There is now a growing body of evidence which could support the idea of making mechanical thrombectomy available to more patients than at present. This could include treating patients with lower NIHSS scores at admission [6][7][8][9], those with more distal occlusions [10][11][12][13][14], patients with larger infarct volumes at presentation [15], and patients presenting more than 6 h after the event [16,17].…”
Section: Introductionmentioning
confidence: 99%